O ensino vocacional no Brasil : a experiência da Escola de Aprendizagem Industrial Américo Renê Giannetti (Uberlândia 1962-1982) - Mundim, Maria Odete Pereira (2005)
The aim of this dissertation is to unveil historical data which are determinative on the creation and pedagogical structuration of Uberlândia Industry Learning Vocational School from 1962 to 1982. Theoretical basis for data analysis were studies on Education History and technical professional teaching in Brazil. Collected data to answer the proposed questions by this search are laws, decrees and decree-laws transcriptions on the creations and pedagogical structuration of the courses offered by the school as well pieces of ACIUB Uberlândia Business and Industry Association written registers, city and state newspapers articles and photos on this search theme, students entrance registers and reports given by the school principle in the studied period. Primary sources are settled in city and state public archives hips, in the 40th Region Teaching Superintendence, in ACIUB, in the René Gianetti School, mainly the interviews with the school ex-principle, Mr. Valdemar Firmino de Oliveira. These collected data allow to observe historical context in which the Uberlândia Industry Learning Vocational School was created and it makes also possible to verify which legal and pedagogical basis this teaching institution was settled on. It was considered, in those days, a region reference concerning to technical and professional education.